The Influence of Unemployment on Poverty Levels in Indonesia - Mustika Johan; Lathiifatul Arifah Febrianti; Imelda Wahyuningtyas; Fuad Salim; Ferdian Dwi Prawira (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This test is carried out based on unemployment as a population problem related to the level of poverty in a country. So increases and decreases will influence each other. In this case, to achieve a level of prosperity and quality of life, regulations are needed in the form of policies to increase production factor resources assisted by all existing actors. This research aims to determine the effect of unemployment on poverty levels in Indonesia, using a quantitative approach and including associative research. The database was taken from the Central Statistics Agency (BPS) page or website using capitalized unemployment data and time series poverty figures per semester from 2008-2022. The research analysis listed uses a simple linear regression test with the SPSS 25 statistical program. The test results obtained are simultaneous and partial. H0 is said to be rejected and H1 is said to be accepted, which means that there is a positive and significant influence of unemployment on poverty levels in Indonesia.